Variations in suprascapular notch morphology and its clinical importance - Gopal, Krishna; Choudhary, Alok Kumar; Agarwal, Jolly; Kumar, Virendra (International Journal of Research in Medical Sciences, 2017)
Background: Suprascapular notch (SSN) is present towards the medial end of superior border of scapula. The morphometric variations of the SSN have been identified. The suprascapular nerve compression is commonly noted at the site of SSN. Methods: The study was carried out in the department of anatomy, SRMS-IMS medical college, Bareilly and SGRRIM-HS Dehradun. The 120 dried scapulae were randomly selected. The age, sex and race of the scapulae were not known. The scapulae were observed carefully for the different shapes of the suprascapular notch. The various dimensions of suprascapular notch were taken by using a digital vernior caliper. Results: In the present study six types of SSN were noted based on the description by Rengachary SS. et al.22 Type I (15.83%); type II (41.66%); type III (25.00%); type iv (12.50%); type v (1.67%) and type VI (3.33%). We also classified the SSN based on the description by M. Polguj et al. 2011,28 the frequencies were: type I (MVD>STD), 20%; type II (MVD=STD=MTD), 3.33%; type III (STD >MVD), 55.83%; type IV (bony foramen), 3.33% and type V (Without a discrete notch), 17.5%. Conclusion: The suprascapular neuropathy may occur at the various anatomical locations of its course and has a variety of causes. Our study is important for clinician because the narrow SSN increase the risk of suprascapular entrapment neuropathy. So the knowledge of these variations should be kept in the mind of clinicians in the diagnosis and treatment of suprascapular neuropathies.